Obstructive sleep apnea causes impairment of the carotid artery in patients with hypertrophic obstructive cardiomyopathy. (April 2019) - Wang, Shengwei; Cui, Hao; Zhu, Changsheng; Wu, Rong; Meng, Liukun; Yu, Qinjun; Huang, Xiaohong; Xiao, Minghu; Wang, Shuiyun
Abstract: Background: Obstructive sleep apnea (OSA) prevalence is high among patients with hypertrophic cardiomyopathy (HCM). OSA can cause increase in carotid intima-media thickness (CIMT) in the general population. However, whether this phenomenon is applicable to patients with HCM is unclear. Methods: A total of 130 consecutive patients with a confirmed diagnosis of hypertrophic obstructive cardiomyopathy (HOCM) at Fuwai Hospital between September 2017 and May 2018 were analyzed. Results: 72 patients (55.4%) were diagnosed with OSA. Patients with OSA were older. Compared to those in patients without OSA, the left, right, and mean CIMTs were significantly increased in patients with OSA. In the multiple linear regression model, age (β = 0.341, p < 0.001), apnea-hypopnea index (AHI) (β = 0.421, p < 0.001), and fasting glucose level (β = 0.167, p < 0.03) were independently associated with mean CIMT increase (adjusted R 2  = 0.458, p < 0.001). In the receiver operating characteristic curve analysis, the area under the curve for CIMT was 0.813 (95% CI, 0.717–0.909, p < 0.001) with a sensitivity and specificity of 0.84 and 0.70 for unexplained syncope, respectively. In the multivariate logistic regression model, we found that the mean CIMT (OR = 10.4, 95% CI = 3.16–34.11, p < 0.001), left ventricular ejection fraction (LVEF) (OR = 0.90, 95% CI = 0.83–0.99, p = 0.03), and amaurosis (OR = 5.07, 95% CI = 1.47–17.49, p = 0.01) were independently associated with unexplained syncope occurrence. Conclusions: In patients with HOCM, CIMT increased with OSA severity. Age, AHI, and fasting plasma glucose level were independently associated with mean CIMT increase. Moreover, amaurosis, LVEF, and higher mean CIMT were independently associated with unexplained syncope in patients with HOCM. Highlights: OSA prevalence is high among patients with hypertrophic cardiomyopathy. OSA can cause CIMT increase in patients with hypertension and general population. In patients with HOCM, the CIMT increased with the severity of OSA. AHI was independently associated with the increase in mean CIMT. Mean CIMT was independently associated with syncope in patients with HOCM.